Relationships between internalized stigma and depression and suicide risk among queer youth in the United States: a systematic review and meta-analysis - Williams, Denise Yookong; Hall, William J.; Dawes, Hayden C.; Srivastava, Ankur; Radtke, Spenser R.; Ramon, Magdelene; Bouchard, D.; Chen, Wan-Ting; Goldbach, Jeremy T. (Frontiers in Psychiatry, 2023)
Background: Queer youth experience high rates of depression and suicidality. These disparities stem from stigma-based stressors, including internalized stigma (i.e., negative social views that minoritized individuals internalize about their own identity). Given the importance of this factor in understanding mental health disparities among queer youth, we completed a systematic review and meta-analysis examining the relationships between internalized stigma and outcomes of depression and suicide risk (i.e., suicidal ideation, non-suicidal self-injury, suicidal behavior).We followed the PRISMA standards. Six bibliographic databases were searched for studies in the United States from September 2008 to March 2022. Dual independent screening of search results was performed based on a priori inclusion criteria.Results: A total of 22 studies were included for data extraction and review. Most studies examined general internalized homophobia, with few examining internalized biphobia or transphobia. Many studies examined depression as an outcome, few studies examined suicidal ideation or behavior, and no studies examined non-suicidal self-injury. Meta-analyses model results show the association between general internalized queer stigma and depressive symptoms ranged r = 0.19, 95% CI [0.14, 0.25] to r = 0.24, 95% CI [0.19, 0.29], the latter reflecting more uniform measures of depression. The association between internalized transphobia and depressive outcomes was small and positive (r = 0.21, 95% CI [-0.24, 0.67]). General internalized queer stigma and suicidal ideation had a very weak positive association (r = 0.07, 95% CI [-0.27, 0.41]) and an even smaller, weaker positive association with suicide attempt (r = 0.02, 95% CI [0.01, 0.03]).Implications for clinical practice, policy, and future research are discussed.